A New Look at Children's Prosocial Motivation. (19th May 2012) - Hepach, Robert; Vaish, Amrisha; Tomasello, Michael
<x xml:space="preserve">Abstract</x> Young children routinely behave prosocially, but what is their motivation for doing so? Here, we review three studies which show that young children (1) are intrinsically motivated rather than motivated by extrinsic rewards; (2) are more inclined to help those for whom they feel sympathy; and (3) are not so much motivated to provide help themselves as to see the person helped (as can be seen in changes of their sympathetic arousal, as measured by pupil dilation, in different circumstances). Young children's prosocial behavior is thus intrinsically motivated by a concern for others' welfare, which has its evolutionary roots in a concern for the well‐being of those with whom one is interdependent.